Cannabis production and land use planning: A literature review - Mathew V. Vaughan; Jeremy Pittman; Sara Epp; Wayne Caldwell (Canadian Planning and Policy, 2021)
Cannabis production standards are evolving with little understanding of their implications on land use planning. Health Canada currently administers a federally-regulated licensing system that does not address odour and light pollution land use impacts across the rural landscape. This literature review addresses the regulatory history of cannabis production in Canada, reviews current production standards, and compares possible cannabis production conflicts with documented land use conflicts from other odourous and light intensive operations to reveal flaws in the existing licensing system. Established cannabis production markets will be examined for further comparisons.